KEDUDUKAN AHLI WARIS TERPIDANA DALAM PENGAJUAN PENINJAUAN KEMBALI BERDASARKAN PUTUSAN MAHKAMAH AGUNG REPUBLIK INDONESIA (STUDI PUTUSAN NOMOR : 97 PK/PID.SUS/2012) - Herri Gunawan Sipayung; Alvi Syahrin; Muhammad Ekaputra; Sutiarnoto Sutiarnoto (Universitas Sumatera Utara, 2018)
ABSTRACT KUHAP (Code of Law of Criminal Procedure) has long been intended to be revised by the government and the Parliament since it is considered not accommodating public interest in getting justice. The research problems are how about the judicial review in law of criminal procedure lodged by a convict’s heir while the convict is still alive and how about the validity of judicial review lodged by a convict’s heir in the regulation No. 97 PK/Pid.Sus/2012 on July 31, 2013 in the name of the convict, ST. The objective of the research is to find out the process of requesting for judicial review in a criminal case, especially the case lodged by a convict’s heir, to explain some experts’ ideas about the legality of requesting for judicial review lodged by a convict’s heir, and to analyze the opinion of the panel of judges about judicial review in the case of ST, the convict. The research used juridical normative referred to legal provisions. Secondary data were gathered by conducting library research and analyzed qualitatively. In the case of ST, the Panel of Judges accepts the request for judicial review lodged by the convict’s wife as the heir while the convict himself is a fugitive. The result of the research shows that the legal consideration of the Panel of Judges in accepting the request for judicial review is that there has been no legal certainty in the KUHAP and in SEMA (the Circular Letter of the Supreme Court) concerning legal remedy done by a convict’s heir. In order to guarantee legal certainty, it is necessary that KUHAP be revised or SEMA be issued to regulate a clear definition of requesting judicial review by a convict’s heir while the convict himself is a fugitive. Keywords: Heir, Convict, Judicial Review